Comparison of Bruch's Membrane Opening Minimum Rim Width and Peripapillary Retinal Nerve Fiber Layer Thickness in Early Glaucoma Assessment - Gmeiner, Jonas M. D.; Schrems, Wolfgang; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Schrems-Hösl, Laura-Maria (Investigative Ophthalmology & Visual Science, 2016)
To compare the diagnostic value of Bruch's membrane opening minimum rim width (BMO-MRW) and retinal nerve fiber layer thickness (RNFLT) in patients with ocular hypertension, preperimetric, and perimetric glaucoma.One hundred eighty-one eyes consisting of 40 healthy controls, 41 ocular hypertensive subjects, 50 subjects with preperimetric glaucoma and 50 with perimetric glaucoma were included. One randomly selected eye was included. All patients underwent slit-lamp examination, funduscopy, achromatic perimetry, and 24-hour IOP profile. Bruch's membrane opening-MRW and RNFLT (3 peripapillary circle scans, 12°/14°/16°) data were obtained using spectral domain optical coherence tomography. Areas under the receiver operating characteristics curves (AUROC) as well as sensitivity at fixed specificity were computed globally and for six vertical split sectors. Venn diagrams were plotted to identify patients that were diagnosed by one of the two parameters only.For RNFLT the smallest circle diameter showed highest diagnostic accuracy and was used for comparison with BMO-MRW. Distinguishing perimetric glaucoma, RNFLT and BMO-MRW showed comparable AUROCs in global (AUROC, 95% confidence interval: 0.954, 0.911-0.996 and 0.929, 0.872-0.986) and sectoral (0.929, 0.877-0.981 and 0.946, 0.904-0.996) analysis. For preperimetric glaucoma BMO-MRW and RNFLT also demonstrated comparable performance in global (0.839, 0.757-0.921 and 0.821, 0.731-0.912) and sectoral (0.860, 0.782-0.938 and 0.835, 0.750-0.920) analysis. When identifying ocular hypertensive eyes AUROCs were lower for global RNFLT and BMO-MRW (0.493, 0.365-0.621 and 0.562, 0.433-0.691). A combined parameter showed an AUROC of 0.959, 0.921 to 0.996 for perimetric and 0.849, 0.770 to 0.929 for preperimetric glaucoma.Bruch's membrane opening-MRW and RNFLT are comparably useful parameters for discrimination of preperimetric and perimetric glaucomatous eyes and show potential to assist each other in glaucoma diagnosis. (www.ClinicalTrials.gov number, NTC00494923; Erlangen Glaucoma Registry.).
EVALuna2:21294